Automated Bakery Management System - S.A.A. Ravishan; E.M.A.I.B. Ekanayaka; B.M. Edirisinghe; N.H. Manimendra; D. I. De Silva; S.M.D.T.H. Dias (International Journal of Engineering and Management Research, 2022)
Providing an automated system to manage the workload of ‘Puzzle’ is the objective of this research. ‘Puzzle’ is a bakery in Sri Lanka. They have been using a handwritten manual system from the origin of the company. They have been able to manage the crowd in the beginning, but with the growing customer crowd, they are having trouble handling their day-to-day workload. Since it is easy, efficient, and effective to have an automated system, they desperately wanted one for their shop. They also mentioned that they do not need a complex system at the beginning since they were used to making use of a manual system, and they wanted to take things slow. After getting used to the new, automated system, they might ask us to add new, complex functionalities such as attendance marking, salary calculation, and leave management. ‘Puzzle’ asked us to add three user types: admin, employee, and customer. Using the respective functionalities for each role will be beneficial for the shop and its users.